Strategy to Prime the Host and Cells to Augment Therapeutic Efficacy of Progenitor Cells for Patients with Myocardial Infarction - Kang, Jeehoon; Kim, Tae-Won; Hur, Jin; Kim, Hyo-Soo (Frontiers in Cardiovascular Medicine, 2016)
Cell therapy in myocardial infarction (MI) is an innovative strategy that is regarded as a rescue therapy to repair the damaged myocardium and to promote neovascularization for the ischemic border zone. Among several stem cell sources for this purpose, autologous progenitors from bone marrow or peripheral blood would be the most feasible and safest cell-source. Despite the theoretical benefit of cell therapy, this method is not widely adopted in the actual clinical practice due to its low therapeutic efficacy. Various methods have been used to augment the efficacy of cell therapy in MI, such as using different source of progenitors, genetic manipulation of cells, or priming of the cells or hosts (patients) with agents. Among these methods, the strategy to augment the therapeutic efficacy of the autologous peripheral blood mononuclear cells by priming agents may be the most feasible and the safest method that can be applied directly to the clinic. In this review, we will discuss the current status and future directions of priming peripheral blood mononuclear cells or patients, as for cell therapy of MI.